EVALUATION OF THE PHYSICAL PROPERTIES OF ECOLOGICAL COMPOSITES OF RECYCLED POLYPROPYLENE AND SISAL FIBER (REMUNOM, 2026)
Growing concerns about sustainability are linked to the production of more sustainable materials, driving interest in environmentally friendly polymer composites. Therefore, the objective of this study was to prepare and characterize sustainable composites based on recycled polypropylene (PPr) and sisal fiber in proportions of 10, 20, and 30%. Density, hardness, and water absorption analyses were performed on the composites formed after extrusion and compression molding. The results demonstrated that the addition of the natural fiber reduced the density and hardness properties of the materials. The addition of the fibrous filler significantly increased the water absorption of the composites formed.